Use of spectroscopic technique to develop a reagent for Mo(VI) utilizing micellar effects on complex formation - KAKI, ESRA HACER (SPRINGER, 2012)
Ultraviolet and visible spectral properties of aqueous solutions of molybdenum(VI) (Mo), gallic acid (GA), Lalanine (Ala), and L-Phenylalanine (Phe), and of their binary and ternary solutions were investigated in the absence and presence of anionic, cationic, and nonionic surfactant micelles. Evaluation of the spectra in a comparative way revealed that both Ala and Phe form ternary complexes with Mo and GA. The formation of a quaternary complex between Mo, GA, Phe, and cetyltrimethylammonium bromide at pH 4.5 provided a reagent system with a strikingly high sensitivity (1.2a (TM) 106 l/(mola (TM) cm)) for use in the spectrophotometric determination of Mo. A mechanism of micellar effects was discussed in terms of the substrate molecular charge and hydrophobicity, and rationalized on the basis of the spectral data obtained above and below the isoelectric pH of the amino acids.
Keywords: UV/Visible spectroscopic analysis; Mo(VI); complexation; micellar effects; SPECTROPHOTOMETRIC DETERMINATION; PROTONATION EQUILIBRIA; MOLYBDENUM; WATER; SURFACTANT; ACIDS; NI2+